(untitled) (Revista Humanismo y Cambio Social, 2022)
This work on global warming causes and effects, constitutes a referential research on the effects that anthropogenic actions linked to profit, insensitivity, lack of ethics and other values, are causing the planet with the indiscriminate use of industrialization, which also includes warming, deforestation, pollution by greenhouse gases, without taking into account the measures to be taken to alleviate, minimize or avoid further damage. Three important variables about the phenomenon of global warming are described: Temperature, deforestation and greenhouse gas emissions.